Økonomisk vækst, produktion og divergens i transitionslandene - Karsten Stæhr (Nordisk Østforum, 2019)
Abstract: Economic growth, production and divergence in the transition countries This article examines developments in income and living standards in the post-communist transition countries. All of these countries had planned economies but differed greatly in their economic and institutional starting points at the time of transition. The extent and speed of reforms has also varied. Production has increased considerably, but many of these transition countries have experienced severe business-cycle fluctuations. Although they have generally narrowed the income gap between them and the world’s richest nations, there are clear signs of divergence, with some of the poorest transition countries making very slow progress here. This is especially the case with the countries of the former Soviet Union and, to a lesser extent, the Balkan countries, but not the 11 countries that have joined the EU. Thus, the economic gains of the post-communist transition have been very uneven across countries.